2000
DOI: 10.1128/aem.66.8.3376-3380.2000
|View full text |Cite
|
Sign up to set email alerts
|

rpoB -Based Microbial Community Analysis Avoids Limitations Inherent in 16S rRNA Gene Intraspecies Heterogeneity

Abstract: Contemporary microbial community analysis frequently involves PCR-amplified sequences of the 16S rRNA gene (rDNA). However, this technology carries the inherent problem of heterogeneity between copies of the 16S rDNA in many species. As an alternative to 16S rDNA sequences in community analysis, we employed the gene for the RNA polymerase beta subunit (rpoB), which appears to exist in one copy only in bacteria. In the present study, the frequency of 16S rDNA heterogeneity in bacteria isolated from the marine e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
272
0
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 384 publications
(286 citation statements)
references
References 31 publications
11
272
0
3
Order By: Relevance
“…Previous studies have suggested that microbial community analysis with a low-copy-number gene may be more accurate than analysis with high-copy-number genes, such as the 16S rRNA gene (Dahllof et al, 2000;Peixoto et al, 2002). Preliminary analysis of the Geobacter sulfurreducens and Geobacter metallireducens genomes indicated that several of the conserved genes used in this study occur as single-copy or low-copy-number genes in the Geobacteraceae.…”
Section: Application To Community Analysis and Environmental Genomicsmentioning
confidence: 99%
“…Previous studies have suggested that microbial community analysis with a low-copy-number gene may be more accurate than analysis with high-copy-number genes, such as the 16S rRNA gene (Dahllof et al, 2000;Peixoto et al, 2002). Preliminary analysis of the Geobacter sulfurreducens and Geobacter metallireducens genomes indicated that several of the conserved genes used in this study occur as single-copy or low-copy-number genes in the Geobacteraceae.…”
Section: Application To Community Analysis and Environmental Genomicsmentioning
confidence: 99%
“…Despite the heterogeneity of 16S rDNA reported previously for other marine isolates (Dahllof et al 2000), all the DILs strains gave a single band on DGGE gel (Fig. 4).…”
Section: Growth Of Cells In Dilution Culturesmentioning
confidence: 85%
“…A total of 7 different strains was found and referenced DILs-1 to DILs-7 (Table 2). Some of the strains were not culturable onto R2Am in primary culture but all were able to grow on this medium in secondary culture (Table 2).Despite the heterogeneity of 16S rDNA reported previously for other marine isolates (Dahllof et al 2000), all the DILs strains gave a single band on DGGE gel (Fig. 4).…”
mentioning
confidence: 83%
“…(6,24). This result can be explained by the intraspecies heterogeneity displayed in a DGGE banding pattern as the result of multiple copies of the ribosomal genes and by the fact that the gene copies have evolved differently (6,24).…”
mentioning
confidence: 99%
“…(6,24). This result can be explained by the intraspecies heterogeneity displayed in a DGGE banding pattern as the result of multiple copies of the ribosomal genes and by the fact that the gene copies have evolved differently (6,24). In order to provide a solution to that issue, some authors had successfully used the rpoB gene, encoding the beta subunit of RNA polymerase which exists in a single copy within the chromosome (6,19).…”
mentioning
confidence: 99%